The Sustainability of Esas Triumvirate for Sustainability-Related Disclosures in the Financial Sector – All for One and One for All? - Rubáček, Filip; MacGregor Pelikánová, Radka; MacGregor, Robert K. (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Sustainability is definitely one of the top priorities of the current highly competitive global society. For almost three decades, the EU has been declaring its commitment to sustainable growth, while progressively recognizing that the concept of shared values, the multi-stakeholder model and corporate social responsibility (CSR) are indispensable. The EU moved, in the context of the COVID-19 pandemic, the war in Ukraine and other events, from mere Directives to Regulations, i.e. the genuine reporting about sustainability is becoming a duty for certain businesses, especially in the financial sector. This political and legislative trend is boosted by the engagement of three special EU institutions (ESAs) entrusted with the development, standardization and monitoring of sustainability-related disclosures based on Regulation 2019/2088. Who belongs in this triumvirate? What are their competencies and tasks? And most importantly, how is this triumvirate and its operations perceived? A holistic multi-disciplinary research of legislative sources and performed surveys and studies yields both quantitative and qualitative data. An open-minded critical analysis of such data, along with a comparison, Socratic questioning and forensic glossing brings answers to these three burning questions and offers fresh recommendations regarding EU pro-sustainability endeavours as well as modern European integration.